Evaluation of the effect of hemodynamic factors on retinal microcirculation by using 3D confocal image-based computational fluid dynamics - Ong, Chi Wei; Tan, Bingyao; Hussain, Shaista; Chuangsuwanich, Thanadet; Braeu, Fabian Albert; Cui, Fangsen (Frontiers in Bioengineering and Biotechnology, 2024)
Purpose. To investigate local hemodynamic changes resulting from elevated intraocular pressure (IOP) in different vasculature networks using a computational fluid dynamics model based on 3D reconstructed confocal microscopic images. Methods. Three-dimensional rat retinal vasculature was reconstructed from confocal microscopy images using 3D U-Net-based labelling technique, followed by manual correction. We conducted a computational fluid dynamics (CFD) analysis on different retinal vasculature networks derived from a single rat. Various venules and arterioles pressures were applied to mimic the effects of elevated intraocular pressure (IOP), a major glaucoma risk factor. An increase in IOP typically correlates with a decrease in venous pressure. We also varied the percentage of capillary dropout, simulating the loss of blood vessels within the capillary network, by reducing the volume of the normal capillary network by 10%, 30%, and 50%. Based on the output of the CFD analysis, we calculated velocity, wall shear stress (WSS), and pressure gradient for different vasculature density. Results Arteriolar pressure, venular pressure, and capillary dropout appear to be important factors influencing wall shear stress in the rat capillary network. Our study revealed that the pressure gradient between arterioles and venules strongly affects the local wall shear stress distribution across the 3D retinal vasculature. Specifically, under a pressure gradient of 3250 Pa, the wall shear stress was found to vary between 0 and 20 Pa, with the highest shear stress observed in region of the superficial layer. Additionally, capillary dropout led to a 25% increase or decrease in wall shear stress in affected areas. Conclusion. The hemodynamic differences under various arterioles and venules pressure, along with different capillary dropout conditions, could help explain the development of various optic disorders, such as glaucoma, diabetic retinopathy, and retinal vein occlusion.